Merunut Makna Kata â€œRefreshingâ€ dan â€œHealingâ€: Kajian Sosiolinguistik - Viktorius P. Feka; Selfiana T. M. Ndapa Lawa; Darius Y. Nama (HINEF : Jurnal Rumpun Ilmu Pendidikan, 2023)
This article aims to explain the differences in meanings between the words "refreshing" and "healing," and to elaborate on how social factors influence the interpretations of these two words. The method used in this research is descriptive-qualitative. Data collection techniques involve questionnaire, interview, and library study. The data is analyzed based on the sociolinguistic approach. The results of the study show that generally people use the words "refreshing" and "healing" without knowing the meanings of these two words. These words are even used interchangeably and are considered recreational words. However, both words have different meanings, either in terms of internal aspects of language (semantics) or in terms of external aspects of language (sociolinguistics). The term "refreshing" literally means "making you feel cooler or less tired"; and, something very different and interesting. The word "healing" is defined as a process of recovery, both physically and emotionally. In a social context, "refreshing" can refer to pleasant and invigorating social interactions; whereas, the word "healing" can reflect the culture of care and social support in certain societies.